Ratapan Iman dalam Tradisi Andung Suku Batak Toba - Pakpahan, Alek (Pastoralia, 2025)
This article examines the andung tradition in Batak Toba culture as an expression of faith, grief, and hope from the perspective of Catholic theology through a literature-based approach. Andung is understood not merely as an emotional lament over death, but as a medium of symbolic communication that embodies spiritual, theological, ecological, and social values in the life of the Batak Toba community. In addition to mourning the loss of loved ones, andung also expresses lament over environmental destruction, such as deforestation, river pollution, the degradation of the Lake Toba ecosystem, and the loss of soil fertility, all of which are understood as consequences of human greed and irresponsibility. In this context, andung becomes a moral call to ecological conversion and the restoration of harmonious relationships between humanity and all of creation. This tradition serves to affirm the dignity of life, strengthen communal solidarity, and provide a space for reconciliation and emotional healing in experiences of grief, including ecological grief. This study shows that andung has a strong correspondence of faith with Catholic spirituality concerning death, eschatological hope, ecological responsibility, and respect for the dignity of both humanity and nature. Through an analysis of theological sources and cultural studies, it is found that andung represents a form of inculturation of faith that reflects the relationship between culture and Christian faith within a pastoral context. Andung affirms that grief is not the end of life, but part of the journey toward the fullness of life in Christ and a calling to care for and restore creation. This study contributes to the development of inculturative theology and enriches the understanding of the faithful in interpreting grief as a spirituality of hope and ecological conversion.